Food Insecurity and COVID-19 Food-Related Perceptions, Practices, and Problems: A 3-State Descriptive Study. (3rd November 2023) - Koyratty, Nadia; Clay, Lauren; Penta, Samantha; Silver, Amber
Abstract: Objective: To compare food insecurity (FI) risk and food-related COVID-19 infection risk perceptions, practices, and problems (3P) in Washington (WA), New York (NY), and Louisiana (LA). Methods: Data from the RAPID Multi-Wave Risk Perception Study was collected via online surveys between May 19 to July 14, 2020 (N = 1260). Multivariable - adjusted logistic and ordinal regressions were performed for odds of FI risk and 3P during these early months of the pandemic. Results: The determinants of FI risk in all states included income, age, and employment. Some determinants were state-specific: households with members at substantial risk for COVID-19 (WA and NY), ethnicity (NY), education, and relationship status (LA). The odds of FI risk were higher among those who perceived higher likelihood of COVID-19 infection via in-store shopping (OR = 1.34, 95% CI: 1.06, 1.70) and improperly cooked food (OR = 1.87, 95% CI: 1.46, 2.41). FI risk was associated with higher odds of problems related to food affordability (OR = 10.66, 95% CI: 7.87, 14.44), preference (OR = 2.51, 95% CI: 1.86, 3.39), sufficiency (OR = 2.63, 95% CI: 1.96, 3.54), food sources (OR = 7.68, 95% CI: 5.73, 10.31), food storage capacity (OR = 0.48, 95% CI: 0.36, 0.66), and knowing where to find help in obtaining food (OR= 7.68, 95% CI: 5.73, 10.31); most of which did not differ by state. No association was found between food insecurity risk and food-related practices. Conclusion: Better food preparedness is needed to reduce FI risk during pandemics in specific groups in WA, NY, and LA. Specifically, food affordability, sufficiency, and storage, as well as sources, and increasing knowledge on food programs are limitations that need to be addressed for emergency situations.